Knowledge and Use of Family Planning Devices among Married Women in Birendranagar, Surkhet - Acharya, Chandra Prakash (Journal of Educational Research and Innovation, 2025)
Family planning is vital for reproductive health and women’s empowerment, yet its use remains uneven in many communities. This study examines the knowledge and use of family planning devices among married women aged 15–49 years in Khorkekhola Tole, Birendranagar–06, Surkhet. Using a qualitative as well as quantitative approach, data were collected from 120 respondents through questionnaires and structured interviews. In the study, 120 women were provided with questionnaire and additionally 7 Health Personals were selected as the participants for FGD. The findings show that although awareness of family planning methods is high, actual use is relatively low, with injectables being the most commonly preferred method. Cultural beliefs, fear of side effects, desire for more children, and limited male involvement were identified as key barriers. The study concludes that a clear gap exists between knowledge and practice, highlighting the need for strengthened health education, improved access to services, and greater spousal communication.